Currency rate and the Cycle of Money theory - Challoumis, Constantinos (Research Papers in Economics and Finance, 2023)
The current paper explains the fundamental concepts of CM theory (Cycle of Money Theory or otherwise known as Cycle Money Theory). The theory of the Money Cycle examines an economy as a whole, therefore the structure of the economy and the distribution of money in the economy is evaluated in terms of how they interact. An economy with a high index of the money cycle indicates prosperity. The current paper demonstrates that tax evasion causes a delay in tax revenue. Tax evasion, on the other hand, has caused economic harm to the economy because money is stored for tax havens rather than the local banking system. Inflation is the economic disease of the inadequate structure of the economy, because of the not appropriate distribution and reuse of money. Functionality (economic activity) and structure of the economy are connected through the way that money moves in an economy or is lost from it. The currency rate in this paper is analyzed based on the theory of the Cycle of Money.